Effectiveness of Collaborative Learning as a Strategy in the Teaching of EFL - Alahdal, Ameen; Hassan Al-Ahdal, Arif Ahmed Mohammed (Opción, 2019)
This paper explored the effectiveness of collaborative learning in EFL classrooms of Saudi Tertiary Education Institutions. The paper used a questionnaire and interviews to elicit quantitative and qualitative data from 40 purposefully selects EFL teachers and learners. The respondents shared their perceptions about how collaborative learning impacted the current pedagogical practices in Qassim University. The study findings highlighted that teachers and students perceived collaborative learning positively in Qassim University. In conclusion, the study found that both students and teachers considered it as the best approach for the learning of a foreign language.